Geological and palaeogeographical peculiarities of the Adamów Graben area, central Poland - Widera, Marek; Dzieduszyńska, Danuta; Petera-Zganiacz, Joanna (Geologos, 2022)
From a geological and palaeogeographical point of view, the area of the Adamów Graben in the vicinity of Turek ranks amongst the best known in central Poland, with several opencast mines located here where lignite was exploited for 57 years. These large-surface exposures provide a good opportunity for detailed geological studies of strata of Late Cretaceous to Holocene age. However, the present research focuses mainly on those deposits, forms and structures that have been most thoroughly examined and are best exposed. These are Cretaceous marls and gaizes, Paleogene ‘blue clays’ and the ‘Koźmin Gravels’, Neogene sandstones, as well as the Quaternary glacial ‘Lake Koźmin’, involutions and ‘Koźmin Las’. Some of these, e.g., the ‘Koźmin Gravels’ and ‘Koźmin Las’, are not known from other Polish territories. Furthermore, results obtained by the authors over a period of nearly 30 years also include data on palaeogeographical changes across some Cenozoic intervals, especially during the early Oligocene and late Weichselian.